Hot Water Pretreatment of Boreal Aspen Woodchips in a Pilot Scale Digester - Jipeng Yan; Shijie Liu (Energies, 2015)
Hot water extraction of aspen woodchips was treated at about 160 °C for 2 h with a liquor-to-solid ratio of 4.76:1 in a 1.84 m3 batch reactor with external liquor circulation. Both five-carbon and six-carbon sugars are obtained in the extraction liquor. Xylose and xylooligomers are the main five-carbon sugar in the hot water extract, which reached a maximum concentration of 0.016 mol/L, and 0.018 mol/L, respectively. Minor monosaccharides including galactose, mannose, rhamnose, glucose, and arabinose are also obtained during the hot water extraction. Rhamnose is the main six-carbon sugar in the extraction liquor, which has a maximum concentration of 0.0042 mol/L. The variations of acetyl groups and formic acid are investigated due to their catalytic effect on the extraction reactions. Zeroth-order kinetics models are found to be adequate in describing the dissolved solids, acids, xylose, and xylooligomers.